Conley index over the base morphism for multivalued discrete dynamical systems - Stolot, Kinga (Topological Methods in Nonlinear Analysis, 2007)
We define an index of Conley type for a certain class ofuppersemicontinuous multivalued dynamical systems, usingtechniques introduced by Mrozek, Reineck and Srzednicki [< i> The Conley index over a base< /i> , Trans.Amer. Math. Soc. < b> 352< /b> (2000), no. 9, 4171–4194]for the index over the base. We give the characterisation of thenontrivial index and present an example, proving that our indexdetects isolated invariant sets that are not detected byKaczyński and Mrozek's [< i> Conley index for discrete multi-valued dynamical systems< /i> ,Topology Appl. < b> 65< /b> (1995), 83–96] index.